Sosialisasi Bahaya Pernikahan Dini Sebagai Salah Satu Upaya Pencegahan Stunting Di SMK Negeri 1 Cipeundeuy - Syahrul Rivaldi; Gia Gustaman; Sri Subekti (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Stunting is a condition where the human height is less than normal according to gender and age. The effects of stunting last a lifetime and even affect the next generation and stunted development in terms of verbal and cognitive motor skills. To prevent stunting, it can be done by implementing socialization of the dangers of early marriage. The target of this activity is students who are in high school. The purpose of holding this activity is to increase students' understanding of the risk of the dangers of early marriage which is one of the factors causing stunting. The method used in this activity is a qualitative observation method with a socialization approach. Data analysis was carried out on the results of the pre-test and post-test to determine whether there was a change in understanding the dangers of early marriage and stunting. The results of this activity indicate that the implementation of socialization on the dangers of early marriage at SMK Negeri 1 Cipeundeuy has an effect on increasing students' understanding of the dangers of early marriage and the risk of impacting stunting.